Selves on display: neoliberal subjectivities in Turkey in the first decade of the twenty-first century through the lens of reality TV shows - Yılmaz, Özlem. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2013., 2013)
This thesis aims to contribute to the studies of neoliberal and postmodern subjectivity by operationalizing the concept of self-display. Self-display is analyzed as a technology of neoliberal subjectification, this latter being indispensable for the sustenance of today’s capitalism. Based on the observation that we are now living in a culture of self-display, which means that we are projecting ourselves as carefully crafted images in order to attain visibility; this thesis tries to understand both this phenomenon, and the society which gave birth to it. It can be said that this study is an attempt to see the society through the window of self-display, and to understand self-display itself, in order to unravel through what mechanisms it is able to function. Out of three sites which open up the fields in which self-display actualizes, namely Reality Shows, social media and the job market, reality shows is chosen. Thus, a Turkish fashion reality show “Bugün Ne Giysem” (What Should I Wear Today) is selected as a case study, which gave us important insights about the mechanisms through which individuals are interpellated to neoliberal subject positions, namely, how these mediums of neoliberal subjectification legitimize themselves, into which desires they intrude and what they offer to the individuals. That neoliberal subjectivity establishes itself by intruding at the level of desire is a well-covered subject in the social sciences literature. This thesis tries to bring in a new aspect of the phenomenon and if possible, to widen the picture, by bringing in the levels of legitimation and satiation side by side with that of desire.
Keywords: Reality television programs -- Turkey.